Intertextual in The Novel Titik Nol by Augustine Wibowo with The Novel Ibuk by Iwan Setyawan - Yuliarti, Yuliarti; Nastiti, Ana Putri (UIR PRESS, 2024)
This research investigates the intertextual aspects in two novels, namely